Power to the parents? Participatory governance, civil society, and the quality of democracy in rural Honduras and Guatemala - Altschuler, D (2010)
This thesis examines whether and how participatory governance (PG), a model for incorporating citizen participation in designing and/or implementing strategies to solve public problems, can strengthen civil society and improve the quality of democracy. The study focuses on community-managed schools (CMS) in Honduras and Guatemala, arguably each country's largest PG initiative, in which parents managed rural schools. This thesis advances a "political capabilities" framework to explore state efforts to strengthen civil society and improve the quality of democracy. I use a mixed-methods approach, centering on surveys of over 2,000 parents and eight community case studies. My research first shows how different long-standing political legacies—“controlled inclusion” in Honduras and “coerced marginalization” in Guatemala—impinged on CMS. In Honduras, patronage networks captured CMS. In Guatemala, community- and national-level polarization contributed to CMS's reversal. Both undermined the CMS model and reduced the likelihood that participants would develop political capabilities. Despite these obstacles to stimulating civil society, I find surprising evidence of important individual-level “spillover” effects—such as gaining skills and increasing participation in other organizations—among a non-trivial minority of participating parents. Moreover, regressions and case study analysis indicate that state support, parents' level of involvement, and parents' perceptions of council effectiveness and democraticness can increase the likelihood of certain spillovers. Still, prior organizational experience remains the best predictor of subsequent participation and leadership. And qualitative analysis further demonstrates the limits of CMS's impacts on rural civil society. For the most part, individuals have not used newly acquired skills to build new types of groups and organize autonomously. Instead, community organizations remain very limited in their scope of action and heavily circumscribed by the state. In sum, this thesis demonstrates how, through one type of PG initiative, states can stimulate participation and produce changes in individuals’ civic and political behavior. But CMS was not a “game-changer” for rural civil society—the link from incremental changes in individual behavior to how rural communities organize themselves and engage with the state remains tenuous.